Biodegradation of Congo Red Dye Using Lysinibacillus Species in a Moving Bed Biofilm Reactor: Continuous Study and Kinetic Evaluation - Maurya K.L.; Swain G.; Kumar M.; Sonwani R.K.; Verma A.; Singh R.S. (My University, 2025)
The objective of this work was to develop a low-cost and efficient biocarrier for biodegradation of azo dye (i.e., Congo red (CR) dye). The potential bacterial species, i.e., Lysinibacillus fusiformis KLM1 and Lysinibacillus macrolides KLM2, were isolated from the dye-contaminated site. These bacterial species were immobilized onto the polypropylene-polyurethane foam (PP-PUF) and employed in a moving bed biofilm reactor (MBBR) for the treatment of CR dye. The effectiveness of the MBBR was investigated by operating the bioreactor in a continuous mode at various initial CR dye concentrations (50–250 mg/L) for 113 days. The removal efficiency was found in the range of 88.4–64.6% when the initial dye concentration was varied from 50 to 250 mg/L. The maximum elimination capacity (EC) of 213.18 mg/L.d was found at 250 mg/L of CR dye concentration. In addition, the CR dye utilization rate in the MBBR was studied by using two kinetics, namely, first-order and second-order (Grau) models. The high regression coefficients (R2 > 0.97) and the satisfactory root mean square (RMSE) values (0.00096–0.02610) indicated the reasonable prediction of CR dye degradation rate by the Grau model. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.